An Evaluation of Vietnam’s Construction Investment Regulatory System Concerning Net-Zero Transition - Dinh, Van Truong; Bui, Duy Anh; Nguyen, Dinh Phong (International Journal of Sustainable Construction Engineering and Technology, 2025)
Vietnam has committed to achieving net-zero carbon emissions by 2050, a target that necessitates transformative changes across all economic sectors, with the construction industry playing a pivotal role due to its significant carbon footprint. This study systematically evaluates Vietnam’s current construction investment regulatory system to assess its readiness and effectiveness in promoting the national net-zero transition. Utilizing desk research and content analysis of relevant laws, decrees, circulars, and technical standards, the research applies the CETEx and OECD frameworks to identify regulatory strengths, weaknesses, and gaps. Findings reveal that while Vietnam has established a foundational legal framework and strategic policies (e.g., Decree 06/2022/ND-CP, Lotus Green Building Certification) for climate action, explicit and binding regulations for net-zero considerations, such as mandatory embodied carbon limits or project-level carbon budgets, are largely absent in investment and permitting processes. Enforcement remains fragmented, particularly at the subnational level, due to capacity deficits. A critical disconnect exists between regulatory mandates and financial incentives, with a notable absence of dedicated green finance instruments (e.g., green bonds, targeted subsidies) and integrated project pipelines to de-risk and scale low-carbon construction. Furthermore, stakeholder engagement lacks formalized, cross-sectoral coordination, and regulatory impact assessments do not consistently integrate climate-focused metrics. The study concludes that despite strong strategic alignment with net-zero ambitions, Vietnam’s construction investment regulatory system faces significant operational hurdles. Recommendations include institutionalizing low-carbon mandates in investment approvals, establishing incentive-based green finance mechanisms, building local implementation capacity, creating an integrated green construction project pipeline and data platform, and strengthening adaptive governance with climate-sensitive regulatory impact assessments. These insights offer a roadmap for policymakers to transform Vietnam’s construction sector into a proactive driver of its net-zero future.